Valor económico del volumen maderable y valor económico del secuestro de CO2 en un bosque de terraza baja del distrito de Andoas, Loreto. 2022 - Arimuya Papa, Karen Milagros (2022)
The economic values of the timber volume and the CO2 sequestration service of the commercial forest species in the low terrace forest, Andoas district, Loreto, Peru, were compared in this study. Data from the forest census of PC1 for forest use permits in native communities and peasant communities were evaluated. The results show that the timber economic value amounts to USD 38 702,95 (USD 61,24/ha). Simarouba amara (USD 8,77/ha and USD 5539,87), Virola elongata (USD 8,58/ha and USD 5424,46) and Ormosia macrocalyx (USD 6,59/ha and USD 4161,71), have higher economic value; while Elaeoluma glabrescens (USD 1,72/ha and USD 1084,73) and Buchenavia macrophylla (USD 0,73/ha and USD 458,73) have lower economic value. The economic value of CO2 sequestration is USD 183 397,98 (USD 290,20/ha). Virola elongata (USD 17 493,10, USD 27,68/ha), Eschweilera bracteosa (USD 170 49.51, USD 26,98/ha) and Calophyllum longifolium (USD 16 767,01, USD 26,53/ha) report higher economic value; while Otoba parvifolia (USD 4540,20, USD 7,18/ha) and Buchenavia macrophylla (USD 3438,65, USD 5,44/ha) present the lowest value. Statistically, a significant difference (? = 0,05) between the averages of the economic value of the timber volume and the economic value of CO2 sequestration was found.